Generation of scaffold incorporated with nanobioglass encapsulated in chitosan/chondroitin sulfate complex for bone tissue engineering - Singh B.N.; Veeresh V.; Mallick S.P.; Sinha S.; Rastogi A.; Srivastava P. (My University, 2025)
Over the past decade, various composite materials fabricated using natural or synthetic biopolymers incorporated with bioceramic have been widely investigated for the regeneration of segmental bone defect. In the present study, nano-bioglass incorporated osteoconductive composite scaffolds were fabricated through polyelectrolyte complexation/phase separation and resuspension of separated complex in gelatin matrix. Developed scaffold exhibits controlled bioreactivity, minimize abrupt pH rise (~7.8), optimal swelling behavior (2.6+–3.1) and enhances mechanical strength (0.62 ± 0.18 MPa) under wet condition. Moreover, in-vitro cell study shows that the fabricated scaffold provide suitable template for cellular attachment, spreading, biomineralization and collagen based matrix deposition. Also, the developed scaffold was evaluated for biocompatibility and bone tissue regeneration potential through implantation in non-union segmental bone defect created in rabbit animal model. The obtained histological analysis indicates strong potential of the composite scaffold for bone tissue regeneration, vascularization and reconstruction of defects. Thus, the developed composite scaffold might be a suitable biomaterial for bone tissue engineering applications. © 2020 Elsevier B.V.